IMPLEMENTING ENGLISH LANGUAGE PROGRAMS IN ISLAMIC BOARDING SCHOOLS: INSIGHTS FROM KRASHEN'S ACQUISITION THEORY - Nadia Rafiah Nawa Kartika; Siti Ulfah Afndoliyah (JF Publisher, 2025)
This study investigates the implementation of English language learning programs at Bumi Cendekia International School, an Islamic boarding school in Yogyakarta, Indonesia. Employing a qualitative descriptive analytical design, the research examines how structured programs and daily English integration facilitate language acquisition for both teachers and students through the lens of Krashen's Language Acquisition Theory. Data were collected through non-participant observations, semi-structured interviews with teachers and administrators, and documentary analysis over three months. The findings reveal a comprehensive approach encompassing three structured programs: Tea Time (weekly showcase activities), English Corner (daily vocabulary practice with peer facilitators called English Ambassadors), and Bumi Cendekia English Pathway (professional development for non-English subject teachers). These programs are complemented by systematic English integration in school announcements, casual conversations, and admission policies requiring English proficiency assessments. The analysis demonstrates substantial alignment with Krashen's theoretical framework, particularly through provision of comprehensible input and reduction of affective filters via engaging, peer-supported activities. The study concludes that this holistic approach, combining structured programs with informal language use while emphasizing teacher development and student engagement, provides a valuable and replicable model for Islamic boarding schools seeking to cultivate English language competencies for global citizenship while maintaining their distinctive religious and cultural identities.